Construction of an exosome-functionalized graphene oxide based composite bionic smart drug delivery system and its anticancer activity. (1st February 2022) - Chen, Qi; Che, Chengchuan; Liu, Jinfeng; Gong, Zhijin; Si, Meiru; Yang, Shanshan; Yang, Ge
Abstract: Graphene oxide has covalently modified by chito oligosaccharides and γ -polyglutamic acid to form GO-CO- γ -PGA, which exhibits excellent performance as a drug delivery carrier, but this carrier did not have the ability to actively target. In this study, the targeting property of breast cancer tumor cell exosomes was exploited to give GO-CO- γ -PGA the ability to target breast tumor cells (MDA-MB-231), and the drug mitoxantrone (MIT) was loaded to finally form EXO-GO-CO- γ -PGA-MIT with an encapsulation efficiency of 73.02%. The pH response of EXO-GO-CO- γ -PGA showed a maximum cumulative release rate of 56.59% (pH 5.0, 120 h) and 6.73% (pH 7.4, 120 h) for MIT at different pH conditions. In vitro cellular assays showed that EXO-GO-CO- γ -PGA-MIT was more potent in killing MDA-MB-231 cells due to its targeting ability and had a significantly higher pro-apoptotic capacity compared to GO-CO- γ -PGA-MIT. The results showed that this bionic nano-intelligent drug delivery system has good drug slow release function and it can increase the local drug concentration of tumor and enhance the pro-apoptotic ability of MIT, so this newly synthesized bionic drug delivery carriers (EXO-GO-CO- γ -PGA-MIT) has potential application in breast cancer treatment.